Anthracnose Fruit Rot of Strawberry - James C. Mertely; Natalia A. Peres (EDIS)
Anthracnose fruit rot is an important disease for strawberry worldwide. Lesions appear as dark, sunken spots on infected fruit. This revised 4-page fact sheet was written by James C. Mertely and Natalia A. Peres, and published by the UF Department of Plant Pathology, September 2012.